In Situ Growth of Au NPs on Nitrogen-Doped Graphene Quantum Dots Decorated Graphene Composites for the Construction of an Electrochemical Immunosensor and Its Application in CEA Detection - Zhengzheng Yan; Lujie Wang; Fei Yan (Molecules)
Carcinoembryonic antigen (CEA) is an important tumor biomarker for the early clinical diagnosis of various cancers, and, therefore, the accurate and sensitive quantitative determination of CEA is of vital significance. In this study, we demonstrated the in situ growth of Au nanoparticles (AuNPs) on nitrogen-doped graphene quantum dots (N-GQDs) decorated reduced graphene oxide (rGO) nanocomposites by using simple drop-coating and electrochemical deposition methods. N-GQDs@rGO can be formed through the π–π stacking interaction and possesses a high specific surface area and many functional groups, providing lots of anchor sites (amino moieties in NGQDs) for the in situ electrochemical growth of AuNPs without the addition of reductants and protective agents. Such AuNPs/N-GQDs@rGO ternary nanocomposites combine the characteristics of three nanomaterials, showing a large surface area, excellent solubility, good conductivity, catalytic activity, a simple fabrication process, and notable stability, which are further used to construct a label-free electrochemical immunosensor for the determination of CEA. Under the optimized experimental conditions, the AuNPs/N-GQDs@rGO-based electrochemical immunosensor achieves a broad linear response, ranging from 1 pg/mL to 0.5 μg/mL and a low detection limit of 0.13 pg/mL. Moreover, the AuNPs/N-GQDs@rGO-based electrochemical immunosensor shows exceptional selectivity, anti-interference, and anti-fouling capabilities for the direct analysis of CEA amounts in fetal bovine serum samples, showing vast potential in the clinical screening of cancer.